The Clinical Efficacy and Safety of Simvastatin in the Management of Portal Hypertension in Cirrhotic Patients: A Systematic Review - Raksheeth Agarwal; Matthew Billy; Oliver Emmanuel Yausep; Radhian Amandito; Vito Filbert Jayalie; Rino Alvani Gani (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2020)
Background: Variceal bleeding is a serious complication of portal hypertension in liver cirrhosis. Current guidelines recommend non-selective beta blockers (NSBBs) and endoscopic variceal ligation for primary prophylaxis of variceal bleeding. However, NSBBs are associated with low response rates and systemic adverse effects. Simvastatin has been shown to reduce portal hypertension in previous studies. Our aim was to assess its clinical efficacy and safety in reducing portal hypertension in cirrhotic patients. Method: We searched PubMed, The Cochrane Library, ScienceDirect, ProQuest, CINAHL, Scopus, and Clinicaltrials.gov, and manually browsed abstracts of major hepatology conferences for selection of studies. We selected randomized controlled trials with a population of cirrhotic patients, simvastatin as an intervention, HVPG change as an outcome, and English as the primary language. The quality of selected studies was assessed using the Cochrane Risk of Bias tool. We extracted change in HVPG from baseline to post-treatment as the principal summary measure, with safety as the secondary outcome.Results: Two full articles were included for qualitative analysis. Both studies reported reductions in HVPG from baseline to post-treatment in the simvastatin group, with this reduction being significantly higher as compared to the control group. Adverse effects were homogenously distributed in both groups, and good safety was reported by both studies. Simvastatin’s HVPG lowering effects are possibly additive to those of NSBBs. Conclusion: Simvastatin effectively reduces HVPG in cirrhotic patients with portal hypertension, although more clinical trials are needed to validate these results. Simvastatin could potentially be combined with NSBBs to achieve greater results.